THE EFFECT OF CASH RATIO AND RETURN ON ASSET ON FIRM VALUE OF CONSTRUCTION COMPANIES SUB SECTOR LISTED ON THE IDX FOR THE 2019-2022 PERIOD - Haikal Farrel Al-Kautsar; Alif Mulya Ardhani; Kholda Atiyatul Maula; Heikal Muhammad Zakaria Hakim (State Islamic Institute (IAIN) Tulungagung, 2023)
The rise of default problems due to poor asset management has an impact on decreasing investor confidence, which affects the value of a company. “This observation aims to examine how the correlation between Cash Ratio and Return on Assets on Company Value is proxied by Price to Book Value, both partially and simultaneously in building construction sub-sector companies with a focus on research for the period 2019 to 2022. This observation makes use of Multiple linear regression as a research method uses SPSS 25 with reference to the classical assumption feasibility test as well as the T-test and F-test. The results of this study show that partially, the cash ratio has a negative but not significant effect on firm value, while return on assets has a positive and significant effect on firm value. Simultaneously, the cash ratio and return on assets together have a positive and significant influence on firm value with a determinant contribution (R Adjusted Square) of 20.5% in explaining the escalation of firm value variables.